O Tribunal Superior Eleitoral e sua comunicação nas redes sociais digitais: uma comparação das eleições de 2014, 2016 e 2018 à luz da lei de acesso à informação e da minirreforma eleitoral de 2015 - Juliana Matos Santos (2018)
The world is increasingly digital, with interference in society and politics. In addition to the use by candidates and parties in the field of political power, it is relevant to observe how the public power, notably the Brazilian Superior Electoral Court, Tribunal Superior Eleitoral (TSE), has used these tools in this sphere of network society interaction. As an expressive framework of how individuals and public life interacted on the Internet, we had the 2016 elections, which were the first in which Article 93-A of Law 9,504 / 1997, created by Law No. 13,165 / 2015, was in force. "The Superior Electoral Court, from April 1st to July 30 of the electoral years, shall promote (...) radio and television advertising, aimed at encouraging women's participation in politics, as well as informing citizens about the rules and functioning of the Brazilian electoral system." It is noted that the internet was not included by law as a mandatory mean for institutional propaganda of TSE, but it is interesting to think of its effectiveness compared to traditional media, considering that the literature about public communication points to the Internet and the digital social networks present in it as spaces for democratic participation. In order to observe the characteristics of TSE communication in digital social networks and the application of the highlighted article, we compared the communication referring to the 2014, 2016 and 2018 elections. Other parameter is the Law on Access to Information, which relate the active transparency that the Law establishes for public Internet sites. The provisions establish that the dissemination of information produced must be in an easily accessible place, as well as the maintenance of a website (§ 2) that contains a research tool; enables the recording of reports in various electronic formats; provide automated access by external systems; disclose in detail the formats used; ensure the authenticity and integrity of available information; keep updated information available; indicate location and instructions that allow the interested party to communicate with the body or entity that owns the site; and adopt the necessary measures to guarantee the accessibility of content for people with disabilities (§3º).